Service robots or human staff? The role of performance goal orientation in service robot adoption. (September 2022) - Tojib, Dewi; Ho, Ting Hin; Tsarenko, Yelena; Pentina, Iryna
Abstract: Understanding the determinants of customer choice between human staff or service robots will assist service firms to encourage service robot adoption and improving their return on investment. Current technology adoption theories fail to consider users' performance goal orientations as a motivational driver, and this is an important omission. In four studies, with participants recruited from market research (M-Turk, Qualtrics) and consumer panels, this research investigates how performance goal orientations – a desire for achievement (PAP) and a desire to avoid failure (PAV) – act as the motivational drivers of service robot adoption. The first study tests the direct effect of PAP and PAV on service robot adoption. The second and third studies test challenge and threat appraisals as mediators between both measured and manipulated PAP and PAV on service robot adoption in different contexts. The final study tests the priming effect of spontaneous social influence on challenge appraisal and how this affects service robot adoption. Findings show that: PAP and PAV have a direct influence on service robot adoption; challenge appraisal mediates the aforementioned relationship; and spontaneous social influence increases challenge appraisal for customers with a PAV orientation. The theoretical and practical implications of these outcomes are discussed in detail. Highlights: Performance approach-oriented customers are more likely to choose robot over human. Challenge appraisal mediates the effect of performance orientation on robot choice. Customer threat appraisal has no effect on the choice of service provider. Social influence increases challenge appraisal for avoidance-oriented customers.